2017
DOI: 10.1038/s41598-017-03360-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Tree Species Ability to Capture and Retain Airborne Fine Particulate Matter (PM2.5)

Abstract: Human health risks caused by PM2.5 raise awareness to the role of trees as bio-filters of urban air pollution, but not all species are equally capable of filtering the air. The objectives of this current study were: (1) to determine the foliar traits for effective PM2.5-capture and (2) explore species-to-species differences in foliar PM2.5-recapture capacity following a rain event. The study concluded that overall, the acicular needle shape made conifers more efficient with PM2.5 accumulation and post-rainfall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
171
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(193 citation statements)
references
References 75 publications
19
171
0
3
Order By: Relevance
“…A. sibirica had grooves around the protrusion to capture more PM2.5 than P. propinqua which lacked these grooves. Pointy protrusions were more efficient than flattened at retaining PM2.5 [68].…”
Section: Mechanisms and Background Techniquesmentioning
confidence: 87%
“…A. sibirica had grooves around the protrusion to capture more PM2.5 than P. propinqua which lacked these grooves. Pointy protrusions were more efficient than flattened at retaining PM2.5 [68].…”
Section: Mechanisms and Background Techniquesmentioning
confidence: 87%
“…Previous research demonstrated that out of 35 woody species studied, all accumulated PM (Mo et al, ). Further, Chen, Liu, Zhang, Zou, and Zhang () suggested that PM 2.5 accumulation capacity increases as a tree matures, and a diverse planting of species augments the trapping of PM 2.5 .…”
Section: The Scientific Benefit Of Treesmentioning
confidence: 99%
“…Another important consideration is that not all trees are equal. Some benefits may be more pronounced in specific species (Chen et al, ; Grote et al, ; Xiao & McPherson, ). Benefits differ within a species as well.…”
Section: Important Considerationsmentioning
confidence: 99%
“…[ [125][126][127][128][129][130][131][132][133] Pesticide runoff mitigation Agroforestry practices can reduce pesticide exposure to pollinators by helping to capture pesticide runoff, prevent or slow pesticide movement through soil, and help break down some pesticides. [134][135][136][137][138] Refuge from pesticides Agroforestry practices may serve as a safe haven for pollinators from pesticides, if adequately protected from spray drift.…”
Section: Habitat Component or Ecosystem Service Summary Key Referencesmentioning
confidence: 99%
“…Although agroforestry practices may influence thermal or vapor drift, no studies were found on this topic. Hedgerows and windbreaks that are 2.5 m-3 m tall, with 40%-50% porosity and fine, evergreen foliage have been shown to be the most effective for droplet drift reduction [125,127,[131][132][133]. Hedgerows with porosity of nearly 75% have also been found to be effective in reducing drift by more than 80% [129].…”
Section: Spray Drift Mitigationmentioning
confidence: 99%